2017
DOI: 10.1177/1534734617696729
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Neutrophil/Lymphocyte Ratio and C-Reactive Protein Levels in Patients With Amputation for Diabetic Foot Ulcers

Abstract: This study compared the effectiveness of the neutrophil/lymphocyte ratio (NLR) versus C-reactive protein (CRP) for evaluating the prognosis and degree of inflammation in patients with amputation for a diabetic foot ulcer (DFU). This study enrolled 56 patients with amputations for DFU with gangrene and compared the CRP levels and NLR measured before and after surgery. Overall, 24 patients (42%) died within 2 weeks postoperatively. Mortality increased with a preoperative/postoperative CRP difference ≤1.5 ( P < .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Given the divergent mechanisms involved in the pathophysiology of these diseases, it might as well be argued that NLR and PLR are mere indicators of a general immune disorder similar to acute phase response. However since their correlation with markers of acute phase response is not consistent across studies, we reason that they probably represent a different aspect/dimension of an immune disorder other than the acute phase response [3,4,[22][23][24].…”
Section: Nlrmentioning
confidence: 87%
“…Given the divergent mechanisms involved in the pathophysiology of these diseases, it might as well be argued that NLR and PLR are mere indicators of a general immune disorder similar to acute phase response. However since their correlation with markers of acute phase response is not consistent across studies, we reason that they probably represent a different aspect/dimension of an immune disorder other than the acute phase response [3,4,[22][23][24].…”
Section: Nlrmentioning
confidence: 87%
“…Other studies have shown that WBC, CRP and ESR are also risk factors of a high amputation rate. 15,18,20,28,32,33 However, controversy still exists. 18,32 34-39 Inflammatory markers are essential tools in the decision-making process for lower extremity infections.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that the severity of DFUs may be in part determined by the deficiency of the immune response in DFUs via deregulation of IL-6, macrophage migration inhibitory factor (MIF), and interferon-inducible protein (IP)-10 [ 118 ], and a compromised neutrophil response [ 119 , 120 , 121 ]. In recent years, it has been proposed that high platelet-to-lymphocyte (PLR) and neutrophil-to-lymphocyte ratios (NLR) may be a biomarker for DFU severity [ 122 , 123 ], where high PLR levels reflect the increased platelet activity, inflammation, and the risk for thrombosis and atherogenesis [ 122 , 124 , 125 ], while high NLR levels lead to the upregulation of cytokines and of proteolytic enzymes that can cause tissue damage [ 122 , 123 ].…”
Section: Pathophysiology Associated With Diabetic Wound Healingmentioning
confidence: 99%